ANALISIS STRUKTUR PASAR BAWANG MERAH VARIETAS LEMBAH PALU DI KABUPATEN SIGI - Muh. Arman Yamin Pagala; Hadayani Hadayani; Yulianti Kalaba (Universitas Tadulako, 2017)
The analysis of market structure of Lembah Palu shallot variety was conducted in Sigi Biromaru Sub District of Sigi District. The research methods used were a Simple Random Sampling and a Snow Ball Sampling technique. Data was analyzed using a market share analysis, a market concentration ratio (CR4) analysis, Herfindahl Hirschman Index (HHI) analysis and a marketing efficiency analysis (margin and farmer’s share). There are four industries dominate the market share of fried shallot of Lembah Palu variety in Sigi regency with MSn (%) of 0.236 for Industry 1, 0.233 for Industry 2, 0.171 for Industry 3 and 0.133 for Industry 4. All indicates that the four industries have a share of 77.3% for buying the Lembah Palu shallot variety with an oligopsony market structure. The value of HHI was 1.098 suggesting that the oligopsony market is at small competing level with high concentration. The obstacles faced by marketing agencies to enter the market were businesscapital and price. The efficiency of marketing channel at channel 1 was 19.956% for its margin and 80.04% for its farmer’s share and at channel 2 19.888% for its margin and 80.11% for its farmer’s share. Keywords : Farmer’s share, Margin, Market concentration, Marketshare, and Obstacles to entering market.